Seed viability of Jatropha curcas in different fruit maturity stages after storage - BAMBANG BUDI SANTOSO; ARIS BUDIANTO; I.D.P. MULIARTA ARYANA (Smujo International, 2012)
Santoso BB, Budianto A, Aryana IGPM. 2012.Seedviability ofJatropha curcasindifferentfruitmaturitystagesafterstorage.Nusantara Bioscience 4:113-117.Theeffect of fruit maturity stages and seed storage period to seed viability was investigated. Seedsamples ofWest Lombok, West Nusa Tenggara genotype ofJatropha curcas were collected fromastandof two-year-old trees at anexperimental field. The seed samples obtained were in four different stages of fruit maturity involving early maturity (green fruit),physiological maturity (yellow fruit), over maturity (brownies fruit), and senescence (black-dry fruit). The results showed that fruitmaturityand storage periodhad an influence on the seed viability ofJ. curcas. Thebest fruit maturity stage for seed viability includingseed oil content was found inyellow fruit and brownies fruit.For germination to be preserved, seeds could be stored in the ambientroom storage for at least five months. For the purpose of oil extraction, seed should preferably be stored not more than four monthsunder ambient room conditions.